An improved method for direct estimation of free cyanide in drinking water by Ion Chromatography-Pulsed Amperometry Detection (IC-PAD) on gold working electrode. (1st February 2018) - Kumar Meher, Alok; Labhsetwar, Nitin; Bansiwal, Amit
Highlights: Direct determination of free cyanide (CN − ) using gold electrode. Advantages over the silver electrode in terms of interfering ion resistance. Lower detection limit (LoD) of 2 µg/L. Demonstration of the proposed method in real drinking water matrices. Abstract: In the present work a fast, reliable and safe Ion Exchange Chromatography-Pulsed Amperometry Detection (IC-PAD) method for direct determination of free cyanide in drinking water has been reported. To the best of our knowledge for the first time we are reporting the application of Gold working electrode for detection of free cyanide in a chromatography system. The system shows a wide linear range up to 8000 µg/L. The electrode was found to have improved sensitivity and selectivity in the presence of interfering ions. The detection limit of the system was calculated to be 2 µg/L. Long term evaluation of the electrode was found to be stable. Reproducible results were obtained from analysis of drinking water samples with recoveries of 98.3–101.2% and Relative Standard Deviations (RSD) of <2%. This study proves the potential application of the newly developed method for the analysis of free cyanide in drinking water.